2021
DOI: 10.3389/fphar.2021.708055
|View full text |Cite
|
Sign up to set email alerts
|

Mitragynine (Kratom)-Induced Cognitive Impairments in Mice Resemble Δ9-THC and Morphine Effects: Reversal by Cannabinoid CB1 Receptor Antagonism

Abstract: Kratom is a widely abused plant-based drug preparation with a global interest in recent years, well beyond its native grounds in Southeast Asia. Mitragynine, its major psychoactive constituent is known to exhibit opioid-like behavioral effects with resultant neuroplasticity in the brain reward system. Its chronic administration is associated with cognitive impairments in animal studies. However, the underlying molecular mechanism for such a deficit remains elusive. In this study, the involvement of cannabinoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 105 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…In the MWM task, mitragynine was shown to impair spatial learning but not reference memory ( Hassan et al, 2019 ). A recent study also showed that chronic escalating high doses of mitragynine led to the impairment of place learning and its reversal using the IntelliCage ® system ( Iman et al, 2021 ). Electrophysiological study also indicated that mitragynine can cause a disruption in hippocampal synaptic transmission and inhibition of LTP induction ( Hassan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the MWM task, mitragynine was shown to impair spatial learning but not reference memory ( Hassan et al, 2019 ). A recent study also showed that chronic escalating high doses of mitragynine led to the impairment of place learning and its reversal using the IntelliCage ® system ( Iman et al, 2021 ). Electrophysiological study also indicated that mitragynine can cause a disruption in hippocampal synaptic transmission and inhibition of LTP induction ( Hassan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the diversity of scientific fields which have profited from the use of IntelliCage underscores the versatility of the system. We present a selection of papers according to clinical criteria in Table 1 and draw attention to useful reviews and discussions of the system using other criteria ( Kiryk et al, 2020 ; Iman et al, 2021a ; Varholick et al, 2021 ).…”
Section: Review Bodymentioning
confidence: 99%
“…Given the high number of divergent IntelliCage papers and topics, we will refrain from discussing them further and we will focus on selected studies showing interesting directions. Readers interested in how the IntelliCage compares to the increasing number of home-cage-based testing systems can find tabulated comparisons ( Kiryk et al, 2020 ; Mingrone et al, 2020 ; Voikar and Gaburro, 2020 ; Iman et al, 2021a ; Coulibaly, 2022 ; Kahnau et al, 2023b ).…”
Section: Review Bodymentioning
confidence: 99%
“…Behavior parameters established using various models of abuse under controlled environmental and drug administration regimens mimic the psychological status of humans in the presence or absence of substances depending on the animal models ( Kumar et al, 2013 ; Kumar et al, 2016 ; Iman et al, 2021 ). Likewise, in opioid dependence animal models, depressive-like behaviors are significant at 1 week after prolonged withdrawal where experiments showed that there was a decreasing level of social interaction and elevation in immobility time which reflects a state of lowered mood or depression-like behavior ( Anraku et al, 2001 ).…”
Section: Opioid Use Disordermentioning
confidence: 99%
“…Apart from that, another prominent withdrawal symptom that accompanies abstinence is impulsive behavior, which encapsulate poor inhibitory response control (impulsive action) and impulsive decision making (impulsive choice) where observations suggest that the opioid system plays a significant role in decision making ( Pattij et al, 2009 ). Morphine exposure also increases motor impulsivity in animal models ( Kieres et al, 2004 ; Colin et al, 2012; Moazen et al, 2018 ), as well as deficits in learning and memory ( Iman et al, 2021 ).…”
Section: Opioid Use Disordermentioning
confidence: 99%